The modern forms of organization of recreational health-building work with a population. - Bondar A.S (Kharkov National Pedagogical University, 2012)
The modern forms of organization are studied recreational health-building employments. Organization of employments in the clubs of fitness, visit of complex sporting buildings is presented. The analysis of publications in which authors examine the features of development of industry of fitness in market conditions is resulted. A questionnaire in which 1500 habitants of city took part in age 18-75 years is conducted. It is set that among polled most popular are clubs of fitness of middle level, where the cost of subscription is made by 20-50 dollars of the USA on a month. It is set that clubs of fitness visit mainly people of middle ages with the purpose of the complex making healthy, maintainance of beautiful physical form and attractive exterior. It is marked that to date clubs of fitness must be oriented mainly on health direction and to satisfy the psychological and social necessities of clients.